Infants with vitamin B12 deficiency-related neurological dysfunction and the effect of maternal nutrition (Annals of Medical Research, 2021)
Aim: Studies linked vitamin B12 deficiency in infancy are most commonly in patients with hematological and dermatological complaints rather than infant with neurodevelopmental retardation. In our study we aimed to evaluate the data of infants who presented with various neurological complaints and determined neurodevelopmental retardation due to vitamin B12 deficiency and also effects of maternal diet on the infants.Material and Methods: Infants who were admitted with various neurological complaints due to vitamin B12 deficiency between the dates of September 2016 and March 2018 were included in this study. Patients were retrospectively analyzed according to age, growth and development, clinical and laboratory findings (neurological, hematologic), continuation of breastfeeding, age at onset of complemantary food. During the pregnancy and lactation, the amount of feeding with animal foods, intake of vitamin supplements, duration of breastfeeding and vitamin B12 levels were examined.Results: The most common complaints were fatigue, pallor, no eye contact, apathy, vomiting, constipation, diarrhea, refusal to feed, retardation to growth and development, undeveloped or lost of ability (ability to tonic neck reflex, ability to sit supported and unsupported ability to sit). In the neurological examination of infants; iIn 13 infants, there was hypotonia, undeveloped ability to tonic neck reflex and ability to sit (supported and unsupported). Fifteen, in 15 infants just undeveloped ability to sit (supported and unsupported) and also in 6 infants had swallowing disorders.Conclusion: Vitamin B12 routinely to all pregnant women like folic acid and iron supplementation. In addition, developmental stages of infants should be evaluated and vitamin supplements should be given to infants when necessary.Keywords: Breastfeeding; Infant; Neurological Findings.
Keywords: Breastfeeding; Infant; Neurological Findings.